Performance analysis of EAC joint GMP inspections (2016–2022): a pathway to strengthening regulatory systems and building capacity in Africa’s less resourced authorities - Mashingia, Jane; Aineplan, Noel; Clase, Kari; Bryn, Steven; Ekeocha, Zita (Frontiers in Medicine, 2025)
IntroductionNational Regulatory Authorities have the responsibility of ensuring that pharmaceutical manufacturers comply with Good Manufacturing Practices (GMP) to ensure that medicinal products are consistently produced according to quality standards. Since July 2016, the EAC National Medicines Regulatory Authorities (NRAs) have been collaborating to conduct joint Good Manufacturing Practice (GMP) inspections. This study was conducted to (a) assess the joint GMP inspection procedure, (b) determine key milestones and target timelines, (c) identify areas of improvement and opportunities for capacity building, and (d) identify the contribution of the EAC joint GMP inspections in the operationalization of the African Medicines Agency (AMA).MethodsA retrospective review of the timelines for joint GMP inspections conducted from 2016 to 2022 was performed using data recorded in the EAC metric tool. Data is captured based on key milestones, including screening, scheduling joint GMP inspections, planning for joint GMP inspections, conducting physical inspections, reviewing GMP documentation, writing inspection reports, peer reviewing inspection reports, reviewing CAPAs, communicating with applicants, and issuing GMP compliance certificates. JMP was used as the statistical software to analyze the main milestones of the EAC joint GMP inspection process. The study also looked into the twinning model and joint inspections for capacity building among NRAs.ResultsResults indicated that a total of 37 pharmaceutical manufacturing facilities, located in Africa, Asia, and Europe, were jointly inspected (35 physical inspections and two desk reviews) between 2016 and 2022. The inspected facilities manufacture vaccines, non-beta-lactam tablets/capsules, sterile products, and other biologicals. Of the 37 facilities inspected, 65% (24) met EAC GMP standards and received a certificate of compliance, valid for 3 years. 8% (3) of the facilities inspected between 2018 and 2022 failed to meet GMP standards and were advised to apply for reinspection. Two facilities have not submitted corrective and preventive action (CAPA) since 2016, and three facilities have not submitted one since 2022. The study further revealed that one facility is pending joint inspection, one has been awaiting CAPA review since 2019, and one with a CAPA is still under review. Two facilities scheduled for physical inspection in 2020 could not be inspected due to COVID-19 travel restrictions. Timelines for key milestones of the joint GMP inspection process showed that overall scheduling of joint GMP inspections took more than 14 workdays, such as 57 days in 2018, 24 days in 2019, 43 days in 2020, and 28 days in 2022. Median times for planning EAC joint GMP inspections aligned with the set timelines of 30 days; however, in 2017, the median duration was 40 days. All physical inspections conducted between 2016 and 2022 were completed within the median timeline of 3 days. Nonetheless, the median time for GMP report writing in 2016 was 16 days, slightly exceeding the established timeline of 14 days. Findings also indicated that manufacturing facilities (Applicants) take a lengthy time to submit CAPA, which should be done within 90 days. Median submission times for CAPA were 135 days in 2018 and 125 days in 2019. In 2022, notable improvements were observed, with applicants submitting CAPA in a median time of 49 days.DiscussionEAC GMP inspections have served as a model for building capacity in lessresourced NRAs through the twinning program. The joint inspections are carried out by two inspectors from more experienced National Regulatory Authorities (NRAs) and one inspector from less-resourced NRAs. These NRAs benefit from learning and gaining practical skills, while also building confidence and trust among themselves. This model is suitable for adoption at the continental level by the African Medicines Agency and the African Medicines Regulatory Harmonization Programme to support reliance, convergence, and harmonization. The study identified several gaps, including incomplete data in the metric tool and a lack of monitoring and recording timelines for joint GMP desk assessments. Based on the findings, the EAC region needs to establish an annual planning mechanism for joint GMP inspections and update the metric tool to include key milestones and timelines for the joint GMP desk assessment process. Enhancing the stakeholders’ feedback mechanism is also essential for reducing delays in submitting corrective and preventive actions (CAPA) from facilities and shortening timelines for the joint regulatory inspection process.